ANALISIS WORK-RELATED MUSCULOSKELETAL DISORDERS (WMSDS) PADA OPERATOR MANUFAKTUR ELEKTRONIK DENGAN PENDEKATAN NORDIC BODY MAP (NBM) & QUICK EXPOSURE CHECKLIST (QEC) - Jingga, Nurha Vina; Lawi, Ansarullah; Mardiansyah, Yopy (JURNAL REKAYASA SISTEM INDUSTRI, 2025)
This study comprehensively evaluates the risk of Work-Related Musculoskeletal Disorders (WMSDs) among production operators at PT EMS, a company engaged in electronics manufacturing. Utilizing a mixed-methods ergonomic approach, the research employed the Nordic Body Map (NBM) to measure operators' subjective complaint levels and the Quick Exposure Checklist (QEC) to assess objective posture-related exposure risks. Analysis of NBM data revealed that the Printing station exhibited the lowest average complaint levels (5.6 total average complaints per operator), indicating better ergonomic conditions. Conversely, Wave Solder and Cutting Point operators reported the highest average total complaints (11.9 and 11.6, respectively), with the Wave Solder station registering the highest proportion of "Severe Pain" cases. The QEC analysis, which focused on the worst-case operator exposure, identified the Wave Solder station as the most critical, yielding the highest Exposure Score of 88% (Action Level 4), followed closely by Printing (78%) and Cutting Point (74%). The body parts most susceptible to injury across these high-risk stations were the Back (QEC score 44), Wrist (40), and Shoulder/Arm (36). The findings confirm that prolonged static posture, repetitive movements, and manual material handling are primary contributors to WMSDs prevalence. Immediate interventions are highly recommended, specifically the provision of push assistance tools, elbow supports, and footrests at the workstation to mitigate exposure risk and enhance occupational health.